Improving Remote Teaching and Online Learning - Maggie Hartnett; Alison Fields (Flexible Learning Association of New Zealand, 2021)
This issue of the Journal of Open, Flexible and Distance Learning (JOFDL) contains an invited piece from a well-known author in the field. The intention is to include an invited piece in subsequent issues. This contribution from Rick Shearer focuses on theory in open, flexible, and distance education. The choice of topic is timely given the experiences of emergency remote teaching (ERT) by teachers and academics over the last 18 months, and the prevailing view that online learning and teaching and ERT are equivalent. In addition to the invited article, this issue has four articles-a descriptive piece and three articles from presentations at the recent FLANZ 2021 Conference.